Maintaining the critical water threshold in degraded Histosols to maximize soybean (Glycine max L. Merr.) growth - Masulili, Agusalim; Sutikarini; Suci, Ida Ayu; Kurniadi, Edi (Journal of Degraded and Mining Lands Management, 2025)
Histosols pose considerable potential for soybean cultivation but are highly susceptible to degradation. One critical constraint is the soil water threshold required to maximize soybean growth. This study aimed to determine the critical soil water content of degraded Histosols amended with rice husk ash and to assess its effect on soybean development. The experiment was conducted in a greenhouse and laboratory at the Faculty of Agriculture, Science and Technology, Universitas Panca Bhakti, from January to March 2024. A randomized complete block design with a factorial arrangement was employed, comprising two factors: rice husk ash at three application rates (12, 18, and 24 t ha-¹) and soil moisture levels at three percentages (25% below field capacity, at field capacity, and 25% above field capacity). Results indicated that leaf water potential, as an indicator of water availability for soybeans, was significantly influenced by soil moisture level. In contrast, rice husk ash treatment did not exert a significant effect. To attain the critical soil water threshold for optimal soybean performance on degraded Histosols, a moisture level 25% above field capacity was required. The best soybean growth was observed under the combined treatment of 12 t ha-¹ rice husk ash and soil moisture 25% above field capacity.